Wind energy integration in Africa: development, impacts and barriers - Haidi, Touria; Cheddadi, Bouchra (Institute of Advanced Engineering and Science, 2022)
The African renewable energy initiative (AREI), adopted in 2015 by nearly half of the African countries, planned to install 10 GW of renewable energy by the end of 2020 and 300 GW by 2030, of which 100 GW would be wind. These countries have each adopted their own national energy strategy defining their rate of renewable electricity capacity, particularly wind, in the overall energy mix by 2020 and/or 2030. This article aims to assess the implementation of these strategies by evaluating the up-to-date achievements in regards to wind energy and thus infer the AREI realization rate by the end of 2020. It focuses on the wind energy investments of the major African countries while comparing their effective realization rates with those targeted by their national strategies. This article also covers the impact of wind energy integration and the barriers to its development in Africa. Taking into account the recent study published in 2020 by the Global Wind Energy Council which assessed the wind energy potential in Africa at 59 TW, the obtained results show that the huge wind power potential in Africa is still far from being exploited and that only Morocco, Egypt and South Africa are on the right track.